2017
DOI: 10.9734/ijtdh/2017/33993
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in a Rural and Urban Community in South-West Nigeria Using Three Different Definitions

Abstract: This work was carried out in collaboration between all authors. Author ENA conceived the study, was involved in data collection, laboratory analysis of blood samples and proof reading of the manuscript. Author OAO supervised the research. Author OAA did the statistical analysis, writing of the methodology and discussion while authors OJ and JS were involved in data collection. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Hossein-Ali et al 40 and Jahangiry et al 41 found that the incidence of MetS was greater in urban areas than in rural areas. Similarly, a greater prevalence of MetS among urban residents has been observed in the Nepalese population, 42 that of South-West Nigeria 43 and in Ecuador’s 44 and in a meta-analysis conducted in the Middle East as epidemiological studies by Ansarimoghaddam et al 45 However, it is difficult to directly compare the results of our research with the above-cited studies’ results. Enlisted literature uses different criteria for the diagnosis of MetSand includes populations demographically, socially, and culturally different and characterized by different SES.…”
Section: Discussionmentioning
confidence: 46%
“…Hossein-Ali et al 40 and Jahangiry et al 41 found that the incidence of MetS was greater in urban areas than in rural areas. Similarly, a greater prevalence of MetS among urban residents has been observed in the Nepalese population, 42 that of South-West Nigeria 43 and in Ecuador’s 44 and in a meta-analysis conducted in the Middle East as epidemiological studies by Ansarimoghaddam et al 45 However, it is difficult to directly compare the results of our research with the above-cited studies’ results. Enlisted literature uses different criteria for the diagnosis of MetSand includes populations demographically, socially, and culturally different and characterized by different SES.…”
Section: Discussionmentioning
confidence: 46%
“…A case-control study of 123 adults with MetS (cases) and age-matched 123 adults without MetS (control) was conducted as previously described. [17] The cases were adults with MetS (from the previous study) while the controls were participants without MetS (from the previous study). [17] Socio-demographic history, blood pressure and anthropometric measurements were documented in a structured questionnaire as earlier reported.…”
Section: Methodsmentioning
confidence: 99%
“…[17] The cases were adults with MetS (from the previous study) while the controls were participants without MetS (from the previous study). [17] Socio-demographic history, blood pressure and anthropometric measurements were documented in a structured questionnaire as earlier reported. [17] The details of the study location, selection of communities and sampling methods have been previously published.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations